Sosialisasi Pencegahan Pernikahan Dini dan Kekerasan pada Anak Remaja di Desa Pasindangan Kabupaten Lebak - Bethary, Rindu Twidi; Setiawan, Ridwan; Ayuningtyas, Ayuningtyas; Pahmulyani, Pahmulyani (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Early marriage is carried out when a person is categorized as not yet an adult according to law no. 16 of 2019, the government has also regulated in law no 23 of 2004 some of the violence that occurs is physical, psychological, sexual violence and neglect in the household. The aim of this service activity is to provide information and knowledge on how to deal with the above problems with preventive action to the elderly teenagers in Pasindangan Village, Lebak Regency. This service activity was carried out at the Madrasah Aliyah Wasilatul Falah with 45 participants. The method in this service is socialization and discussion about preventing early marriage and sexual violence. The results of this activity received a positive response from the school because students gained knowledge and understanding of the impact and prevention of early marriage and sexual violence. Another prevention that can be done in the school environment is needed the teacher’s approach to students and the active role of the family and community, so that a generation of quality youth can be created, both in terms of education and social. So it can be concluded that there is a role significant increase in understanding of department roles and functions human resources to the audience.